2006
DOI: 10.1128/jvi.80.5.2495-2505.2006
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alternative Splicing Isoform of Human T-Cell Leukemia Virus Type 1 bZIP Factor (HBZ-SI) Targets Distinct Subnuclear Localization

Abstract: Adult T-cell leukemia (ATL) is associated with prior infection with human T-cell leukemia virus type 1 (HTLV-1); however, the mechanism by which HTLV-1 causes adult T-cell leukemia has not been fully elucidated. Recently, a functional basic leucine zipper (bZIP) protein coded in the minus strand of HTLV-1 genome (HBZ) was identified. We report here a novel isoform of the HTLV-1 bZIP factor (HBZ), HBZ-SI, identified by means of reverse transcription-PCR (RT-PCR) in conjunction with 5 and 3 rapid amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
130
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 34 publications
5
130
1
2
Order By: Relevance
“…Nos résultats prouvaient le contraire. Depuis, nous avons pu montrer avec d'autres que HBZ est produite majoritairement dans les cellules infectées à partir d'un transcrit épissé [11][12][13]. Il est intéressant de noter que vu leur structure primaire (Figure 2), les ARNm de Tax et HBZ ne sont quasiment pas complémentaires, ce qui exclut qu'ils aient un effet antisens l'un sur l'autre.…”
Section: Hbz La Protéine Oubliéeunclassified
“…Nos résultats prouvaient le contraire. Depuis, nous avons pu montrer avec d'autres que HBZ est produite majoritairement dans les cellules infectées à partir d'un transcrit épissé [11][12][13]. Il est intéressant de noter que vu leur structure primaire (Figure 2), les ARNm de Tax et HBZ ne sont quasiment pas complémentaires, ce qui exclut qu'ils aient un effet antisens l'un sur l'autre.…”
Section: Hbz La Protéine Oubliéeunclassified
“…A unique feature is its transcription from the 3′ LTR in an antisense direction [1]. Two isoforms, spliced and unspliced, are expressed that encode transcription factors with a basic leucine zipper (bZIP) domain, which differ slightly in the N-terminal region [6]. HBZ was first reported to down-regulate HTLV-1 transcription, which is activated by Tax, i.e., HBZ antagonizes the function of Tax (Figure 1).…”
Section: Hbz Is a Unique Gene With Novel Functionsmentioning
confidence: 99%
“…[18][19][20] More recent reports showed that the new splice isoform of the transcript is not only more abundant but also functionally more important than the other type of transcript. 21,22 HBZ is reported to have an effect on the increased proliferation of infected cells.…”
Section: Preferential Expansion Of Htlv-1-infected CD 4 T Cellsmentioning
confidence: 99%